The Role of Ruangguru Online Tutoring in Islamic Religious Education (PAI) Learning for Madrasah Ibtidaiyah Students - Susanto Susanto; Misbahul Khairani; Noor Malihah; Ferli Septi Irwansyah (Faculty of Education and Teacher Training of UINSI Samarinda, 2026)
This study examines the role of Ruangguru online tutoring in supporting Islamic Religious Education (PAI) learning among students at MI Al-Azhar Samarinda. Using a qualitative field research design, data were collected through observation, in-depth interviews, and documentation. Participants consisted of seven students who actively used Ruangguru for PAI learning, seven parents, one Ruangguru branch manager, and one marketing officer, selected purposively to represent student, family, and platform perspectives. Data were analyzed using the interactive model of Miles, Huberman, and SaldaÃ±a, including data condensation, data display, and conclusion drawing. The findings show that Ruangguru in Samarinda operates through an e-learning model centered on the Ruangngaji feature. This feature provides animated PAI learning videos, infographic summaries, Ruang Uji practice exercises, and learning progress reports. Ruangguru supports PAI learning by improving students’ understanding and learning outcomes, providing accessible learning facilities, increasing motivation and enthusiasm, helping students overcome difficulties in Qur’anic recitation and related materials, and enabling students to access learning resources anytime and anywhere. The study indicates that online tutoring platforms can serve as complementary learning resources for PAI at the madrasah ibtidaiyah level. However, broader studies involving different schools, platforms, and learning contexts are needed to strengthen the generalizability of these findings.